P38 Decision regret in men treated for localised prostate cancer: results from the life after prostate cancer diagnosis study. (2nd September 2017) - Downing, A; Wright, P; Watson, E; Wagland, R; Hounsome, L; Butcher, H; Gavin, A; Glaser, AW
Abstract : Background: Men with localised prostate cancer have a number of treatment options. Treatments carry associated benefits and side- and late-effects. The Life After Prostate Cancer Diagnosis study is a UK-wide survey of men 18–42 months post-diagnosis of prostate cancer. The survey included treatment questions, the Decision Regret Scale (DRS) and a single item on decision-making participation. The aim of this sub-study is to explore the association of decision regret with prostate cancer treatment and patient perception of participation in decision making. Methods: The English arm of the survey achieved a 60.3% response rate (30 465 respondents). Men diagnosed with stage 1–3 disease were included in this sub-study (n=16, 808). Descriptive statistics were used to explore associations between DRS scores (0–100), self-reported treatments and perceived participation in decision-making. Results: 12 600 (75.0%) men completed the DRS. Due to the skewed nature of the data, decision regret was categorised as 'None' (score=0; 36.5%), 'Low' (score=5–20; 31.6%) and 'High' (score=≥25; 31.8%). Levels of regret were lowest in men who underwent brachytherapy alone and surgery alone (25.8% and 27.5% respectively reporting 'High' regret). Men who received combination therapy (e.g. radiotherapy and hormones) reported higher levels of regret compared to men having a single therapy (34.8% vs. 28.3% reporting 'High' regret). 28.6% of men on active surveillance reported a high level of regret. 74.2% of men said their views were definitely taken into account in treatment decisions: 22.6% of these reported high regret. 2.8% of men said their views were not taken into account; 62.8% reported high regret. Conclusion: These preliminary analyses show a strong association between perceived involvement in treatment decision making and subsequent decision regret in men with prostate cancer. Levels of regret also vary according to the type of treatment received. Interestingly, men on active surveillance who receive no treatment report similar levels of regret to those who undergo surgery. Further analysis will investigate the impact of patient characteristics and functional outcomes (urinary, bowel and sexual) on levels of regret.